2018
DOI: 10.3389/fmicb.2018.00464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Verbenone Conversion From cis-Verbenol by Gut Facultative Anaerobes of Dendroctonus valens

Abstract: Since its introduction from North America, Dendroctonus valens LeConte has become a destructive forest pest in China. Although gut aerobic bacteria have been investigated and some are implicated in beetle pheromone production, little is known about the abundance and significance of facultative anaerobic bacteria in beetle gut, especially with regards to effects of oxygen on their role in pheromone production. In this study, we isolated and identified gut bacteria of D. valens adults in an anaerobic environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…Plant defensive compound such as α-pinene serves as a precursor of verbenone, a common bark beetle anti-aggregation pheromone 75 , 76 . The biochemical pathway of verbenone production from cis-verbenol is recently documented to be mediated by enzymes originated from facultative anaerobes in D. valens gut (red turpentine beetle) under the frass-simulated and gut-simulated oxygen concentration environment 77 . Our present findings also endorse such possibilities; however, that requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Plant defensive compound such as α-pinene serves as a precursor of verbenone, a common bark beetle anti-aggregation pheromone 75 , 76 . The biochemical pathway of verbenone production from cis-verbenol is recently documented to be mediated by enzymes originated from facultative anaerobes in D. valens gut (red turpentine beetle) under the frass-simulated and gut-simulated oxygen concentration environment 77 . Our present findings also endorse such possibilities; however, that requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the abundances of Enterobacter (Figure 4a) and Klebsiella (Figure 4d) were higher in May than in January. Adult D. valens emerge and then spread to new hosts via a pheromone-mediated mass attack from mid-May to mid-June [42]. May is close to the time of eclosion; thus, the increases in the abundances of these bacteria may be related to the preparation for beetle pheromone production.…”
Section: Discussionmentioning
confidence: 99%
“…Although various aspects of the gut microbiome of the RTB have been investigated widely [38][39][40][41][42][43][44], it is unclear whether seasonal changes in temperature alter the composition of the gut microbiome, and if changes in the microbiome are interconnected with changes in the host physiology. We hypothesize that overwintering influences the composition of the gut microbiome of RTB, and these changes can have physiological consequences.…”
Section: Introductionmentioning
confidence: 99%
“…These extra 20 bacterial species, including Acinetobacter sp., Comamonas testosterone , Asaia platycodi , and Gluconobacter cerinus , may acquire from food when beetles colonize pine trees when compared to dispersal beetles. Here, we did not compare bacterial compositions between the two sexes of D. valens , mainly because our previous results have shown that male and female have similar gut microbiota compositions using both culture-dependent and high-throughput pyrosequencing methods [16,34,36].…”
Section: Discussionmentioning
confidence: 99%